2016
DOI: 10.1089/jayao.2015.0051
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, Attributions, and Emotions Toward Endocrine Therapy in Young Women with Breast Cancer

Abstract: Young women's views regarding ET may play an important role in determining adherence behavior. Given that young women have a higher risk of recurrence, some of which may be attributable to ET non-adherence, further work is needed to confirm these findings and determine whether interventions designed to modify young women's perceptions of ET could promote adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…We found that women under age 50 were less likely to be adherent to ET. These findings are consistent with the literature on ET usage [8], which suggests that younger women have unique considerations in their ET decision-making framework, including fertility [20] and reluctance to believe ET was a necessary part of their breast cancer treatment [21]. These explanatory factors are not fully understood and warrant further research [22].…”
Section: Resultssupporting
confidence: 77%
“…We found that women under age 50 were less likely to be adherent to ET. These findings are consistent with the literature on ET usage [8], which suggests that younger women have unique considerations in their ET decision-making framework, including fertility [20] and reluctance to believe ET was a necessary part of their breast cancer treatment [21]. These explanatory factors are not fully understood and warrant further research [22].…”
Section: Resultssupporting
confidence: 77%
“…Women who were high risk were more likely to report being nonadherent. 42 Negative and positive emotions regarding therapy were related to decreased and increased adherence, respectively, 35 , 68 and perceived importance of therapy was related to increased adherence. 61 Karmakar 69 found that coping appraisal, defined as the effectiveness of taking HT and self-efficacy in ability to take HT, minus the costs of taking HT, was associated with increased odds of adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies found no effects of necessity beliefs on adherence. 27 , 40 , 46 , 68 These four studies had small sample sizes and may have lacked power to find a significant effect. However, where effect sizes were given, they were relatively small.…”
Section: Resultsmentioning
confidence: 99%
“…We have tried to explain this result as an indirect effect of depression with ET-specific factors, since the effects of self-efficacy and medication beliefs on medication adherence are known. High self-efficacy, high positive beliefs on medication, and low negative beliefs on medication are more likely to lead to adherence to prescribed medications [ 5 , 11 , 30 ]. Several studies which focused on self-efficacy and medication beliefs as mediators linking depression and medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, these efforts have mainly focused on identifying determinants of AET adherence. Few studies have addressed the relationships among the factors [ 6 , 30 ]. We designed a research framework based on the hierarchical model of AET adherence determinants [ 8 ] and a determinants of adherence model that was developed for dyspepsia medication [ 12 ].…”
Section: Discussionmentioning
confidence: 99%